Aquaman [videorecording (DVD)] - Momoa, Jason; Heard, Amber, 1986-; Dafoe, Willem; Wilson, Patrick, 1973- (Warner Bros. Home Entertainment, 2019)
An action-packed adventure that reveals the origin story of half-human, half- Atlantean Arthur Curry and takes him on the journey of his lifetime--one that will not only force him to face who he really is, but also to discover if he is worthy of who he was born to be: a king.